Functional promoter polymorphisms direct the expression of cystathionine gamma-lyase gene in mouse models of essential hypertension. (January 2017) - Gupta, Vinayak; Kapopara, Piyushkumar R.; Khan, Abrar A.; Arige, Vikas; Subramanian, Lakshmi; Sonawane, Parshuram J.; Sasi, Binu K.; Mahapatra, Nitish R.
Abstract: Despite the well-known role of cystathionine γ-lyase (Cth) in cardiovascular pathophysiology, transcriptional regulation of Cth remains incompletely understood. Sequencing of the Cth promoter region in mouse models of genetic/essential hypertension (viz. Blood Pressure High [BPH], Blood Pressure Low [BPL] and Blood Pressure Normal [BPN] mice) identified several genetic variations. Transient transfections of BPH/BPL- Cth promoter-reporter plasmids into various cell types revealed higher promoter activity of BPL- Cth than that of BPH- Cth . Corroboratively, endogenous Cth mRNA levels in kidney and liver tissues were also elevated in BPL mice. Computational analysis of the polymorphic Cth promoter region predicted differential binding affinity of c-Rel, HOXA3 and IRF1 with BPL/BPH- Cth promoter domains. Over-expression of c-Rel/HOXA3/IRF1 modulated BPL/BPH- Cth promoter activities in a consistent manner. Gel shift assays using BPH/BPL- Cth -promoter oligonucleotides with/without binding sites for c-Rel/HOXA3/IRF1 displayed formation of specific complexes with c-Rel/HOXA3/IRF1; addition of antibodies to reaction mixtures resulted in supershifts/inhibition of Cth promoter-transcription factor complexes. Furthermore, chromatin immunoprecipitation (ChIP) assays proved differential binding of c-Rel, HOXA3 and IRF1 with the polymorphic promoter region of BPL/BPH- Cth . Tumor necrosis factor-α (TNF-α) reduced the activities of BPL/BPH- Cth promoters to different extents that were further declined by ectopic expression of IRF1; on the other hand, siRNA-mediated down-regulation of IRF1 rescued the TNF-α-mediated suppression of the BPL/BPH- Cth promoter activities. In corroboration, ChIP analysis revealed enhanced binding of IRF1 with BPH/BPL- Cth promoter following TNF-α treatment. BPL/BPH- Cth promoter activity was diminished upon exposure of hepatocytes and cardiomyoblasts to ischemia-like pathological condition due to reduced binding of c-Rel with BPL/BPH- Cth -promoter. Taken together, this study reveals the molecular basis for the differential expression of Cth in mouse models of essential hypertension under basal and pathophysiological conditions. Graphical abstract: Highlights: Cystathionine γ-lyase (CTH) is a crucial regulator of cardiovascular diseases. This study reports transcriptional regulation of CTH in mouse models of hypertension. Promoter variations govern the CTH transcription depending on the physiological context. Ischemia-like pathological condition reduces the CTH expression via diminished binding of c-Rel. TNF-α modulates the CTH gene expression via enhanced expression of IRF1.